HPV Vaccine Uptake, Willingness to Receive, and Causes of Vaccine Hesitancy: A National Study Conducted in Saudi Arabia Among Female Healthcare Professionals - AlShamlan NA; AlOmar RS; AlAbdulKader AM; Shafey MM; AlGhamdi FA; Aldakheel AA; AlShehri SA; Felemban LA; AlShamlan SA; Al Shammari MA (International Journal of Women's Health, 2024)
Nouf A AlShamlan,1 Reem S AlOmar,1 Assim M AlAbdulKader,1 Marwa Mahmoud Shafey,1 Faisal A AlGhamdi,2 Abdullah A Aldakheel,2 Saud A AlShehri,2 Lyana A Felemban,3 Shahad A AlShamlan,2 Malak A Al Shammari1 1Department of Family and Community Medicine, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 3College of Medicine, Fakeeh College of Medical Sciences, Jeddah, Saudi ArabiaCorrespondence: Nouf A AlShamlan, Department of Family and Community Medicine, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia, Tel +966504901406, Email nashamlan@iau.edu.saBackground: Epidemiological evidence has shown that human papillomavirus (HPV) is the most frequent cause of sexually transmitted infection, and vaccination is an essential measure to prevent associated diseases and complications. This study aimed to assess the HPV vaccine uptake and its associated factors as well as HPV vaccine hesitancy by female healthcare workers (HCWs) in Saudi Arabia.Methods: This online, questionnaire-based, cross-sectional study involved female HCWs in Saudi Arabia between July and October 2022. The study tool included questions about sociodemographic, occupational, and reproductive characteristics, uptake of HPV vaccination, and reasons of hesitancy. Chi-squared and t-tests were used for bivariate analyses, and multivariable logistic regression was used to adjust for confounders.Results: The total number of participants was 1857. Around 20% of HCWs received at least one dose of the HPV vaccine, and around 45% were willing to take it this year. Lower odds of vaccine uptake were reported among older participants and those with a higher level of education. However, nurses, HCWs with a previous HPV infection, those with a family history of cervical cancer, or those with a previous cervical cancer screening test had higher odds of receiving the vaccine. On the other hand, older participants and diploma degree holders were less willing to take the HPV vaccine. Higher odds of willingness were reported in married HCWs, those with a previous HPV infection, those who received a previous HPV vaccine dose, or those who were screened for cervical cancer. Lack of knowledge and some misconceptions were the most reported reasons for hesitancy.Conclusion: Certain factors that affect HCWs personal decisions to take the vaccine were identified. By targeting these issues, epidemiologists, public health officials and women’s health care providers can work to increase HPV vaccine uptake and reduce the burden of HPV-related diseases in this population.Keywords: HPV vaccine, epidemiology, public health, women’s health, healthcare worker, uptake